Basic principles of curriculum and instruction - Tyler, Ralph W. (Ralph Winfred) 1902-1994 (The University of Chicago Press, 2013)
Presents the concept that curriculum should be dynamic, a program under constant evaluation and revision. This book shows how educators can approach curriculum planning, studying progress and retooling when needed. It explains that curriculum planning is a continuous, cyclical process, an instrument of education that needs to be fine-tuned.